Coal bottom ash as a low cost adsorbent for removing dye pollutant / Nor Fadilah Mohamad ...[et al.] - Mohamad, Nor Fadilah; Abdul Rani, Noor Hidayu; Mohd Zopri, Aini Sofia; Noor Azman, Muhammad Naqib Saifullah
The thermal power plant waste material, coal bottom ash (CBA) was utilized as a potential adsorbent for the dye removal. The effectiveness of coal bottom ash (CBA) and activated coal bottom ash (ACBA) waste material in adsorbing dyes from aqueous solutions was studied as a function of contact time and the effect of adsorbent dosage. The performance of coal bottom ash (CBA) and activated coal bottom ash '(ACBA) were carried out by using of two basic dyes namely-Methylene blue (MB) and Methyl Red (MR) due to their dyes removal efficiency. Coal bottom ash (CBA) was dried up by using oven at 105°C for 24 hour to remove moisture contents and further kept in furnace at temperature of 500°C for 6 hour in presence of air. Adsorption studies was carried out by batch technique for 50 mL of stock solution with initi.al concentration of 16 mg/L of methylene blue (MB) and 13.5 mg/L of methyl red (MR) respectively. The optimum for contact time for the methylene blue (MB) on both adsorbents is 3 hours for 7.09% of CBA and 20.58% of ACBA whereas it only took 1 hour of the contact time for methyl red (MR) with both adsorbents (61.28%) and (78.53%) to reach higher adsorption. The higher uptakes of both dyes removal efficiency were found at 3 gram where methylene blue were 90.32% for CBA and 95.91% for ACBA and for the methyl red were 83.09% for CBA and 91.34% for ACBA. The increase of amount of adsorbent were increase the amount of dye uptakes due to the adsorbent sites and surface area that contact with the dyes and consequently leads to a better adsorption. The present study showed that the use of coal bottom ash (CBA) as an adsorbent would provide an effective on colour removal of dye solution.